The effects of Crocus sativus L. (Saffron) and its ingredients on dietary intakes in cardiovascular disease in Iranian population: A systematic review and meta-analysis - Kianmehr, Majid; Mahdizadeh, Fateme; Khazdair, Mohammad Reza (Frontiers in Nutrition, 2022)
Cardiovascular disease (CAD) is a one of most common causes of mortality around the world. The aim of this study is summarize and conclude the clinical evidence regarding the use of Crocus sativus (C. sativus) and its ingredients on cardiovascular risk factors. A systematic search was conducted with PubMed, Web of Science (ISI) and Scopus in the English language until September 2021. A fixed-effect or random-effects models were applied to pool standard mean difference (SMD) and its 95 % confidence intervals (CI). Randomized controlled studies that assessed the clinical effects of C.sativus and its ingredients on dietary intake (Energy, Carbohydrate, Protein and total Fat) in human subjects were included. Six studies comprising 421 participants were included in the meta-analysis. Pooling of results showed significant effect of saffron on total fat (-0.14; 95% CI: -0.49 to 0.20; I2 = 57.3%) and significant effect of crocin on Energy (0.94; 95% CI: -0.77 to 2.65; I2 = 95.9%), Carbohydrate (0.44; 95% CI: -0.74 to 1.62; I2 = 92.6%), Protein (-0.04; 95% CI: -0.26 to 0.34; I2 = 0.0%). Present meta-analysis suggests that treatment with crocin is more efficacious than saffron in energy, carbohydrate, protein, while in fat, saffron is more efficacious than crocin. However, further studies are needed to confirm these findings.